Micro-UFO (Untethered Floating Object): A Highly Accurate Microrobot Manipulation Technique - Uvet, Huseyin; Demircali, Ali Anil; Kahraman, Yusuf; Varol, Rahmetullah; Kose, Tunc; Erkan, Kadir (MDPI, 2018)
A new microrobot manipulation technique with high precision (nano level) positional accuracy to move in a liquid environment with diamagnetic levitation is presented. Untethered manipulation of microrobots by means of externally applied magnetic forces has been emerging as a promising field of research, particularly due to its potential for medical and biological applications. The purpose of the presented method is to eliminate friction force between the surface of the substrate and microrobot. In an effort to achieve high accuracy motion, required magnetic force for the levitation of the microrobot was determined by finite element method (FEM) simulations in COMSOL (version 5.3, COMSOL Inc., Stockholm, Sweden) and verified by experimental results. According to position of the lifter magnet, the levitation height of the microrobot in the liquid was found analytically, and compared with the experimental results head-to-head. The stable working range of the microrobot is between 30 mu m to 330 mu m, and it was confirmed in both simulations and experimental results. It can follow the given trajectory with high accuracy (<1 mu m error avg.) at varied speeds and levitation heights. Due to the nano-level positioning accuracy, desired locomotion can be achieved in pre-specified trajectories (sinusoidal or circular). During its locomotion, phase difference between lifter magnet and carrier magnet has been observed, and relation with drag force effect has been discussed. Without using strong electromagnets or bulky permanent magnets, our manipulation approach can move the microrobot in three dimensions in a liquid environment.
Keywords: microrobots; untethered microrobotic manipulation; diamagnetic levitation; DELIVERY; MOTION; Chemistry; Science & Technology - Other Topics; Instruments & Instrumentation; Physics